2020
DOI: 10.3390/ma13071491
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Zoom® Whitening Product in Human Fibroblasts

Abstract: Tooth whitening procedures are increasing; however, side effects can occur, such as damage to pulp cells, by the whitening products. This study aims to assess the cellular effects promoted by a whitening product, namely, the oxidative stress fostered by the active agent hydrogen peroxide, with and without photoactivation. Additionally, if cellular recovery occurred, we intended to determine the time point where cells recover from the tooth whitening induced damage. Human fibroblasts were exposed to hydrogen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The mouse fibroblast NIH/3T3 cell line is one of the widely employed cell lines most sensitive to chemicalinduced cytotoxicity in toxicity tests of dental materials 40) . Cell-based cytotoxicity tests are a widely accepted methodology for testing dental materials' cytotoxicity, with fibroblast cells being a convenient and reproducible model, as listed by ISO/EN10993-5 [41][42][43] .…”
Section: Cell Viability Of Gel Ha-abalone 20 Wt%mentioning
confidence: 99%
“…The mouse fibroblast NIH/3T3 cell line is one of the widely employed cell lines most sensitive to chemicalinduced cytotoxicity in toxicity tests of dental materials 40) . Cell-based cytotoxicity tests are a widely accepted methodology for testing dental materials' cytotoxicity, with fibroblast cells being a convenient and reproducible model, as listed by ISO/EN10993-5 [41][42][43] .…”
Section: Cell Viability Of Gel Ha-abalone 20 Wt%mentioning
confidence: 99%
“…Tooth whitening is one of the most frequently chosen procedures to restore the esthetics of discolored teeth. Whitening can be performed both in the dental clinic and at home [ 126 , 127 ]. Hydrogen peroxide (H 2 O 2) is the most commonly used substance for this purpose due to its low price and high effectiveness [ 83 ].…”
Section: Whiteningmentioning
confidence: 99%
“…Interestingly, hydrogen peroxide can diffuse through the enamel to a concentration of about 0.01% in the pulp. Recent studies suggested that the higher the content of whitening agents such as hydrogen peroxide, the greater the cytotoxic effect on the pulp [ 127 ]. Cytotoxicity increases significantly after using a LED lamp with a wavelength from 400 to 505 nm.…”
Section: Whiteningmentioning
confidence: 99%
See 2 more Smart Citations